Real‐life experience of guselkumab in patients with psoriasis. Issue 6 (14th July 2020) - Snast, Igor; Sherman, Shany; Holzman, Roie; Hodak, Emmilia; Pavlovsky, Lev
Abstract: High levels of efficacy were demonstrated in randomized controlled trials assessing the efficacy of guselkumab; however, real‐life data are lacking. In this retrospective cohort study, we assessed the efficacy and safety of guselkumab in a cohort of psoriasis patients heavily pretreated with biologic agents. Primary efficacy endpoint was the percentage of patients achieving ≥psoriasis area and severity index (PASI) 90 response at week 24. The cohort included 33 patients of mean age 60 ± 13 years. Guselkumab was initiated after a mean of 4.0 ± 1.0 prior biologics failed over a mean period of 7. 4 ± 3.8 years. The mean duration of guselkumab treatment was 9.5 ± 3.7 months; 29 patients completed at least 24 weeks of treatment. At week 24, 22 patients (76%) achieved response of PASI 75 or higher, 18 (62%) achieved PASI 90 or higher, five (17%) PASI 100, and seven (24%) ≤PASI 50. No adverse effects were observed. This study confirms the efficacy and safety of guselkumab in real‐world clinical practice, although for a lesser degree compared with clinical trials.